2018
DOI: 10.1038/s41598-018-28031-7
|View full text |Cite
|
Sign up to set email alerts
|

7B2 chaperone knockout in APP model mice results in reduced plaque burden

Abstract: Impairment of neuronal proteostasis is a hallmark of Alzheimer’s and other neurodegenerative diseases. However, the underlying molecular mechanisms leading to pathogenic protein aggregation, and the role of secretory chaperone proteins in this process, are poorly understood. We have previously shown that the neural-and endocrine-specific secretory chaperone 7B2 potently blocks in vitro fibrillation of Aβ42. To determine whether 7B2 can function as a chaperone in vivo, we measured plaque formation and performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 50 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Support for this mechanism has been presented for clusterin, BRICHOS proteins, and cytoplasmic sHsps ( Rohne et al, 2016 ; Chen et al, 2017 ; Mogk et al, 2019 ) and recent work shows similar properties for GRN-C ( Bhopatkar et al, 2020 ) and for proSAAS ( Peinado et al, 2020 ). In addition, the finding of reduced plaque number in AD model mice lacking 7B2 expression ( Jarvela et al, 2018 ) or clusterin ( DeMattos et al, 2002 ; Wojtas et al, 2017 ) suggests possible roles for 7B2 and clusterin in sequestration events ( Figure 1 , right panel).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Support for this mechanism has been presented for clusterin, BRICHOS proteins, and cytoplasmic sHsps ( Rohne et al, 2016 ; Chen et al, 2017 ; Mogk et al, 2019 ) and recent work shows similar properties for GRN-C ( Bhopatkar et al, 2020 ) and for proSAAS ( Peinado et al, 2020 ). In addition, the finding of reduced plaque number in AD model mice lacking 7B2 expression ( Jarvela et al, 2018 ) or clusterin ( DeMattos et al, 2002 ; Wojtas et al, 2017 ) suggests possible roles for 7B2 and clusterin in sequestration events ( Figure 1 , right panel).…”
Section: Discussionmentioning
confidence: 99%
“…However, among AD patients, contradicting studies have reported either a slight increase ( Winsky-Sommerer et al, 2003 ) or no change ( Iguchi et al, 1987a ) in 7B2 levels. APP transgenic mouse brains also do not show alterations in 7B2 levels, indicating that 7B2 is not upregulated during the course of disease ( Jarvela et al, 2018 ). Majerova et al (2017) showed increased levels of CSF 7B2 in proteomic studies of a tauopathy transgenic rat model of AD.…”
Section: B2 and Prosaasmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, highly conserved multifunctional 14-3-3 proteins ( Cornell and Toyo-oka, 2017 ) complement protein C1q ( Benoit and Tenner, 2011 ), essentially participating in neural development and neuroprotection. 7B2 precursor ( Jarvela et al, 2018 ), cathepsin B ( Hook et al, 2020 ), and heat shock protein 70 ( Turturici et al, 2011 ) were detected as ApKHC1 cargo is involved in Parkinson’s disease, Alzheimer’s disease, polyglutamine diseases, and amyotrophic lateral sclerosis. Therefore, the present study validates the synaptic mechanics as well as the cellular significance of kinesin motor protein in directional intracellular transport in response to learning-induced memory formation.…”
Section: Discussionmentioning
confidence: 99%